Factor XI deficiency: incidental diagnosis post coronary artery bypass graft. Issue 1 (February 2014) - Lammy, Simon; Pessotto, Renzo
Severe Factor XI (FXI) deficiency is defined when the activated partial thromboplastin time is prolonged and its activation is <1–15 UdL −1 in plasma. It is inherited as an autosomal recessive trait but can be acquired. In severe deficiency the bleeding diathesis is normally injury related. This particularly occurs during surgical procedures and trauma involving tissues rich in fibrinolytic activators. Cardiopulmonary bypass induces transient abnormalities in haemostasis which can cause a postoperative bleeding diathesis. Once treated, it does not appear to be a contraindication to cardiac procedures. Conversely, acquired deficiencies are more insidious being incidentally diagnosed during routine laboratory investigations and might be triggered by an inhibitory agent. We present a case of an uncomplicated 12-month delayed diagnosis of Factor XI deficiency following coronary artery bypass grafting and sternal rewiring. The potential risks if undiagnosed and the uncharacteristic clinical history of our case are discussed.